Hydraulic Performance of Inverted Siphons for Irrigation Water Supply Using Physical Modeling - Zulfan, James; Ginting, Bobby Minola (International Journal of Integrated Engineering, 2022)
In this paper, we investigated the performance of the Rambatan siphons in Indramayu Regency, Indonesia, via physical modeling. The model was built in the laboratory with a scale of 1:10, consisting of two siphons, each with a diameter of 0.3 m and a length of 14 m for the model scale. Several scenarios were considered for the physical modeling, of which the focus was on analyzing the discharge capacity, sediment flushing, flow pattern, and pressure. Using the (prototype) design discharge of 6.36 m3/s and some variations of sediment size for the original configuration of the model, we observed the insufficient hydraulic capacity of the siphons. Several modifications were thus applied to the original design, namely by modifying the upstream channel and extending the upper wall of the downstream channel. The result showed that the hydraulic performance increased after applying such modification scenarios, where the siphons were able to discharge 6.36 m3/s. In addition, we observed that the flushing pipe diameter of 0.5 m was faster to flush the sediment inside the siphons. The results of this study are useful for the related stakeholders to increase water supply productivity.